Global-Local Seismic Performance Discrepancy in Top-Heavy Adaptive Reuse Buildings on Soft Soil - Yusuf, Nabil Mochammad; Wibowo, Ari; Anggraini, Retno (Rekayasa Sipil, 2026)
Adaptive reuse of existing high-rise buildings often introduces severe vertical mass irregularities, particularly when functional changes significantly increase live loads. Unlike previous studies that typically isolate the effects of vertical irregularity or soft soil, this research distinctly quantifies the compounded detriment of top-heavy adaptive reuse, specifically on soft soil sites. This study conducts a forensic seismic assessment of a 15-story reinforced concrete frame that was converted from an office to an archive storage facility, where live loads increased from 2.4 kN/m² to 7.18 kN/m² on the upper floors. Using Nonlinear Static Procedures according to ASCE 41-17 with semi-rigid diaphragm modeling, the structural response is evaluated under Site Class SE conditions. The analysis reveals a "Gravity Strangle" mechanism, where excessive gravity loads from the archive storage consume a significant portion of the primary beam capacity before seismic excitation. The results demonstrate a critical discrepancy: while the global roof drift (1.56%) suggests safe Immediate Occupancy (IO) performance, the maximum inter-story drift spiked to 3.18% at the transition floors. Component-level analysis further reveals that 35% of primary beams at this level suffer severe plastic hinge rotations. These findings confirm that for top-heavy buildings on soft soil, relying solely on global drift indicators is deceptive. The study advocates for mandatory nonlinear component-level verification in future adaptive reuse codes to prevent brittle soft-story failures.